Effect of phosphorus doses and mycorrhizal fungi on mineral nutrition and growth of 'Cleopatra' mandarin (Citrus reshni Hort ex Tan.) - Rocha, Mara Rúbia da; de Oliveira, Elizabeth; de Carvalho, Gilmarcos (Pesquisa Agropecuaria Brasileira, 1994)
This study was carried out to verify the effects of phosphorus doses an inoculation with a mixed population of vesicular-arbuscular mycorrhizal fungi on growth and mineral nutrition of 'Cleopatra' mandarin until transplanting. The plants were grown in trays containing commercial substrate, inoculated with a mixed population of Acaulospora morrowae, Glomus clarum and Glomus etunicatum and noninoculated substrate which received six phosphorus doses (0, 320, 640, 1280, 2000 and 2560 g P2O5/m3 of substrate) supplied as simple superphosphate. The inoculation promoted better plant growth, and increased the boron contents in the shoots. The inoculated plants presented larger growth and reached average height of 12.30 cm at four months after sowing, when they were ready to be transplanted.
Keywords: Glomus etunicatum; Glomus clarum; Acaulospora morrowae; rootstock